Spatial and temporal variation of phytoplankton in hot spring of Atri, Odisha, India - Dash, A; Panda, S S; Palita, S K; Patra, H K; Dhal, N K (Current Botany, 2013)
Seasonal dynamics of phytoplanktons along with various physicochemical parameters were recorded in the hot spring of Atri, Odisha during the year 2010-2011. The study was carried out to ascertain the phytoplanktons diversity in relation to the changing physico-chemical parameters in an extreme condition of the hot spring on seasonal basis. Total twenty eight genera having forty two species of phytoplanktons were recorded under the following classes, viz. Chlorophyceae, Cyanophyceae Bacillariophyceae and Euglenophyceae. Chlorophyceae was found to be dominating class contributing 40% of the total. The highest numbers of phytoplankton species were recorded during summer season with an average of 11, 3,000 cells/liter. Dominant species identified were Anabaena aequalis, Closterium ehrenbergii Meneghini ex Ralfs, Eudorina sp., Merismopedia punctata Meyen, Microcystis aeruginosa (Kützing) Kützing, Navicula membranacea Cleve, Oscillatoria sp., Pediastrum simplex Meyen, Scenedesmus quadricauda Chodat. Correlation studies of phytoplankton with physicochemical variables indicate a significant positive correlation with chlorophyll-a, alkalinity and nitrate concentration at p≤0.01 and p≤0.05.